Endometrial thickness measurements among Asherman syndrome patients prior to embryo transfer. Issue 12 (21st October 2020) - Movilla, Peter; Wang, Jennifer; Chen, Tammy; Morales, Blanca; Wang, Joyce; Williams, Alexandria; Reddy, Himabindu; Tavcar, Jovana; Loring, Megan; Morris, Stephanie; Isaacson, Keith
Abstract: STUDY QUESTION: Is there an association between endometrial thickness (EMT) measurement and clinical pregnancy rate among Asherman syndrome (AS) patients utilizing IVF and embryo transfer (ET)? SUMMARY ANSWER: EMT measurements may not be associated with successful clinical pregnancy among AS patients undergoing IVF. WHAT IS KNOWN ALREADY: Clinical pregnancy rate after IVF is significantly lower in patients with a thin endometrium, defined as a maximum EMT of <7 mm. However, AS patients often have a thin EMT measurement due to intrauterine scarring, with a paucity of data and no guidance on what EMT cutoff is appropriate when planning an ET among these patients. STUDY DESIGN, SIZE, DURATION: This is a retrospective cohort study of 45 AS patients treated at a specialized advanced hysteroscopic clinic from 1 January 2015, to 1 March 2019. PARTICIPANTS/MATERIALS, SETTING, METHODS: Review of EMT measurements prior to a total of 90 ETs, among 45 AS patients. The impact of the maximum EMT measurement prior to ET on clinical pregnancy rate was analyzed. MAIN RESULTS AND THE ROLE OF CHANCE: A total of 25/45 (55.6%) AS patients ultimately went on to have ≥1 clinical pregnancy following a mean ± SD of 2.00 ± 1.26 ET attempts. There was a total of 90 ETs among the 45 AS patients, with 29/90 (32.2%) ETs resulting in a clinical pregnancy. Younger patient age ( P = 0.05) and oocyte donation ( P = 0.01) were the only variables identified to be significant predictors for a positive clinical pregnancy outcome on bivariate analysis. The mean EMT measurement prior to all ETs among AS patients was 7.5 ± 1.6 mm. EMT measurement prior to ET did not predict a positive clinical pregnancy on either bivariate ( P = 0.84) or multivariable analysis (odds ratio 0.91, P = 0.60). 31.8% of EMT measurements measured <7.0 mm. In this small cohort, no difference in the clinical pregnancy rate was detected when comparing ETs with EMT measurements of <7.0 mm versus ≥7.0 mm ( P = 0.83). The mean EMT measurement decreased with increasing AS disease severity; 8.0 ± 1.6 mm for mild disease, 7.0 ± 1.4 mm for moderate disease and 5.4 ± 0.1 mm for severe disease. LIMITATIONS, REASONS FOR CAUTION: Our small sample size limits our ability to draw any definitive conclusions. In addition, patients utilized various infertility clinics. This limits our ability to evaluate the consistency of EMT measurements and the IVF care that was received. WIDER IMPLICATIONS OF THE FINDINGS: EMT measurement cutoff values should be used with caution if canceling a scheduled ET in AS patients. STUDY FUNDING/COMPETING INTEREST(S): This study was not funded. K.I. reports personal fees from Karl Stroz and personal fees from Medtronics outside the submitted work. The other authors have no conflicts of interest. TRIAL REGISTRATION NUMBER: N/A.